Determinants of Diabetic Peripheral Neuropathy: A Multivariable Analysis Among Patients With Type 2 Diabetes Mellitus - Zaqqi Ubaidillah; Sindi Amala Putri; Chairul Huda AL Husna; Muhammad Nur Cahyo Firdaus (Care : Jurnal Ilmiah Ilmu Kesehatan, 2026)
Diabetic peripheral neuropathy (DPN) is one of the most common chronic complications of diabetes mellitus and a major contributor to foot ulceration, lower-extremity amputation, and reduced quality of life. Early identification of modifiable risk factors is essential to improve preventive strategies and reduce disease burden. The study aims to identify factors associated with diabetic peripheral neuropathy among patients with diabetes mellitus. A cross-sectional study was conducted among 120 patients with diabetes mellitus. This study uses an accidental sampling technique. Diabetic peripheral neuropathy was assessed using the Michigan Neuropathy Screening Instrument (MNSI), which consists of an objective foot examination, a 128-Hz tuning fork test, and a 10-g monofilament test. Knowledge level was examined using modified questionnaire Diabetic Foot Knowledge Scale. Bivariate associations were analyzed using the chi-square test, and variables with significant associations were entered into a multivariable binary logistic regression model to identify independent predictors. Statistical significance was set at p 0.05. Among the participants, 48 (40.0%) had diabetic peripheral neuropathy. Bivariate analysis showed significant associations between neuropathy and blood glucose level (p = 0.002), diabetes knowledge (p = 0.021), and duration of diabetes (p = 0.017), whereas age, smoking status, and medication adherence were not significantly associated. In the multivariable analysis, blood glucose level remained the strongest independent predictor of neuropathy (adjusted odds ratio [AOR] = 0.220, 95% confidence interval (CI: 0.080–0.608; p = 0.003), followed by diabetes knowledge (AOR = 0.423, 95% CI: 0.190–0.945; p = 0.036) and duration of diabetes (AOR = 0.405, 95% CI: 0.182-0.901; p = 0.027). Blood glucose level, diabetes knowledge, and duration of diabetes were independently associated with diabetic peripheral neuropathy. These findings highlight the importance of optimizing glycemic control, strengthening diabetes education, and implementing routine neuropathy screening to facilitate the early identification of high-risk patients and support preventive diabetes care.